Cardiovascular risk in individuals with inflammatory bowel disease - Biondi, Robertha Baccaro [UNESP]; Salmazo, Pericles Sidnei [UNESP]; Bazan, Silméia Garcia Zanati [UNESP]; Hueb, João Carlos [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; Sassaki, Ligia Yukie [UNESP] (Taylor & Francis, 2020)
Background: Inflammatory bowel disease (IBD) patients present a higher risk of develop-ing cardiovascular diseases due to the presence of chronic inflammation, which plays an essential role in atherogenesis. Therefore, the aim of the study was to evaluate the cardiovascular risk between patients with IBD and healthy control individuals. Materials and Methods: A total of 52 consecutive IBD outpatients from a tertiary hospital and 37 healthy controls were enrolled. Data collected included age, sex, smoking status, presence of comorbidities, disease activity, ongoing medical treatment, body mass index, arterial blood pressure, and cardiovascular risk. The cardiovascular risk was based on the Framingham risk score and ultrasonography variables, such as the carotid intima-media thickness and the presence of atherosclerotic plaque in the carotid. Multivariate logistic regression or multiple linear regression analysis was performed at a significance level of 5%. Results: No differences were observed between groups with regard to age, sex, smoking status, comorbidities, blood pressure, body mass index, lipid profile, and Framingham risk score. In the IBD group, fasting glucose [95 (86.2–107.3) mg/dL vs 86 (79–100) mg/dL, p=0.041], carotid intima-media thickness (0.69±0.12 mm vs 0.63±0.12 mm, p=0.031), and atherosclerotic carotid plaque (25% vs 5.4%, p=0.032) were higher compared with those in the control group. Multivariate logistic regression analysis showed that patients with IBD presented a 6.45-fold higher risk of carotid atherosclerotic plaque (odds ratio: 6.45; 95% confidence interval: 1.035–40.216; p<0.046). Conclusion: Patients with IBD are at an increased risk of atherosclerosis and, consequently, an increased risk for cardiovascular diseases.
Keywords: Cardiovascular risk; Carotid artery diseases; Carotid intima-media thickness; Inflammatory bowel disease